Stroking characteristic variations in the 100-m freestyle for males of differing skill - Chollet, D.; Pelayo, P.; Delaplace, C.; Tourny, C.; Sidney, M. (Perceptual and Motor Skills, 1997)
Summary.-The purpose of the study was to identify the stroking characteristics such as race and length used by male swimmers of differing skill and to analyze the variations of velocity, stroke rate, and stroke length during the course of the race. The performance of 442 male subjects including 40 swimmers compering at an international 100-m freestyle event was videotaped and later analyzed to measure velocity, stroke rate, and stroke length on each lap of the race. Stroke length seemed to be the best predictor of swimming velocity. Different levels of performance could be discriminated by the variations of velocity, stroke rate, and especially stroke length throughout the race. Besides higher values for velocity, stroke rate, and stroke Iength, the best swimmers were characterized by the capacity to maintain these parameters constant throughout the course of the race. Such results could be used by coaches to assess technique and training for certain racing strategies.